Seamus Heaney - Vendler, Helen 1933-
Helen Vendler traces Heaney's invention as it evolves from his beginnings in Death of a Naturalist (1966) through his most recent volume, The Spirit Level (1996). In sections entitled "Second Thoughts," she considers an often neglected but crucial part of Heaney's evolving talent: self-revision. Here we see how later poems return to the themes or genres of the earlier volumes, and reconceive them in light of the poet's later attitudes or techniques Vendler surveys all of Heaney's efforts in the classical forms - elegy, genre-scene, sonnet, parable, confessional poem, poem of perception - and brings to light his aesthetic and moral attitudes.